Advancements in the application of modified biochar for the removal of heavy metals and organic pollutants: short review (International Journal of Scientific Research and Management (IJSRM), 2024)
Water pollution, primarily caused by heavy metals and organic pollutants, poses a significant threat to environmental and public health. Traditional water treatment technologies, while effective, often face limitations such as high costs and secondary pollution. This review explores the advancements in the application of modified biochar for the removal of heavy metals and organic pollutants from contaminated water. We begin by discussing the various preparation methods of biochar, emphasizing the modifications that enhance its adsorption capabilities. The use of biochar in adsorptive removal of heavy metals is examined, highlighting the mechanisms and efficiencies involved. Additionally, the role of biochar-based adsorbents in the removal of organic pollutants is analyzed, focusing on adsorption processes and the incorporation of photocatalytic properties. The review also delves into biochar-based catalysts in sulfate radical-based advanced oxidation processes (AOPs), showcasing their potential in degrading complex organic pollutants. Furthermore, the application of biochar-based adsorbents in binary pollutant systems is reviewed, providing insights into their multifunctional capabilities. The paper concludes with future perspectives, suggesting pathways for further research and development to enhance the effectiveness and applicability of biochar in water treatment technologies. The findings underscore the promise of modified biochar as a versatile and sustainable solution for mitigating water pollution